Revisiting Arabic Grammar Instruction: An Experimental Study on the Pedagogical Application of Antoun Dahdah’s Linguistic Framework - Gilang Mahirul Mursyid (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Arabic grammar instruction is often perceived as complex and cognitively demanding due to its abstract and rule-based nature. This study revisits Arabic grammar instruction by examining the pedagogical application of Antoun Dahdah’s linguistic framework, which emphasizes the visual and systematic organization of grammatical rules. Using a quasi-experimental design, the study was conducted at a public Islamic senior high school (MAN 1 Lamongan, Indonesia) and involved two intact eleventh-grade classes: an experimental group taught using Dahdah’s framework and a control group taught through conventional instruction. The instructional focus was on fiʿl muḍāriʿ mansūb and majzūm. Data were collected through pre-tests and post-tests to measure grammar achievement and a questionnaire to examine students’ perceptions. The results showed a significant difference in post-test scores in favor of the experimental group. Normalized gain analysis indicated that the Dahdah-based instruction was moderately effective in improving students’ grammatical competence. In addition, students reported highly positive perceptions toward the clarity and organization of the instructional framework. These findings suggest that Antoun Dahdah’s linguistic framework offers a pedagogically valuable approach to reorganizing Arabic grammar instruction in secondary education.